Computer modeling of water purification in bioplateau taking into account biodegradation processes and greenhouse gas emissions (Моделювання, керування та інформаційні технології, 2025)
The authors’ research concerns the equations of filtration of contaminated water with dispersed particles of organic residues. A review of works, formulation of research tasks and a mathematical model of filtration with consideration of clogging and suffusion processes and biodegradation are carried out. Dependencies for estimating the volume of greenhouse gases released as a result of biodegradation of organic pollution are proposed.Дослідження авторів стосуються рівнянь фільтрації забрудненої води з дисперсними частинками органічних решток. Проведено огляд робіт, постановку задач дослідження та побудовано математичну модель фільтрації з урахуванням кольмотаційно-суфозійних процесів та процесів біодеградації.